Adolescents' health and health behaviour as predictors of injury death. A prospective cohort follow-up of 652,530 person-years - Nummi Tapio; Koivusilta Leena; Parkkari Jari; Mattila Ville M; Kannus Pekka; Rimpelä Arja (BMC, 2008)
Abstract Background Injuries represent an important cause of mortality among young adults. Longitudinal studies on risk factors are scarce. We studied associations between adolescents' perceived health and health behaviour and injury death. Methods A prospective cohort of 57,407 Finns aged 14 to 18 years was followed for an average of 11.4 years. The end-point of study was injury death or termination of follow-up in 2001. The relationships of eight health and health behaviour characteristics with injury death were studied with adjusted Cox's proportional hazard model. Results We identified 298 (0.5%) injury deaths, 232 (0.9%) in men and 66 (0.2%) in women. The mean age at death was 23.8 years. In the models adjusted for age, sex and socioeconomic background, the strongest risk factors for injury death were recurring drunkenness (HR 2.1; 95% CI: 1.4-3.1) and daily smoking (HR 1.7; 95% CI: 1.3-2.2). Poor health did not predict injury death. Unintentional and intentional injury deaths had similar health and health behavioural risk factors. Conclusion Health compromising behaviour adopted at adolescence has a clear impact on the risk of injury death in adulthood independent from socioeconomic background. On the other hand, poor health as such is not a significant predictor of injury death. Promotion of healthy lifestyle among adolescents as part of public health programmes would seem an appropriate way to contribute to adolescent injury prevention.